PENGEMBANGAN MODEL MATERI AJAR BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) - Etsa Purbarani; Liliana Muliastuti; Siti Farah (BASA Journal of Language & Literature, 2021)
Until now, the number and variety of BIPA teaching materials are still minimal. BIPA teaching materials that have been authorized by the Ministry of Education and Culture of the Republic of Indonesia cannot be said to meet the intended communication needs. Grammar, language skills, and cultural materials are delivered integratively, but learning activities in it have not fully bridged foreign learners to be able to communicate in Indonesian appropriately by paying attention to the context, society, and culture of Indonesia. This creates problems for foreign learners. Foreign learners have found that the Indonesian learned in the classroom is different from the use of Indonesian in society. Foreign learners may get high grades in class, but lack confidence, understanding, and communication competence in Indonesian. Based on the situation, this study focuses on developing a CEFR-based BIPA teaching material model by integrating aspects of communication, cultures, connections, comparison, and communities. These five aspects are known as the 5Cs and are an important foundation in learning foreign languages, one of which is Indonesian. By integrating these five aspects in listening, speaking, reading, writing, and grammar teaching materials, foreign learners can master Indonesian language competence better and comprehensively. In addition, foreign learners are also encouraged to master the competence of communicating in Indonesian more appropriately so that there is no missing link between the Indonesian learned in class and the Indonesian that are actually used in society. The teaching material model developed will focus on the B1 or early intermediate level because at that level BIPA learners have begun to be able to understand, discuss, and communicate about more abstract topics such as non-material cultural topics related to collective logic, habits, and traditions.